Culture, benevolent and hostile sexism, and entrepreneurial intentions - Stedham, Yvonne; Wieland, Alice (International Journal of Entrepreneurial Behavior & Research, 2017)
Purpose In this study, the authors relate cultural masculinity to individual level sexist beliefs (hostile and benevolent sexism) and gendered entrepreneurial stereotypes. The purpose of this paper is to explore whether hostile and benevolent sexism affect entrepreneurial intentions and whether this relationship is mediated by gendered entrepreneurial stereotypes. Design/methodology/approach The proposed relationships are explored using a sample of 192 participants from the USA and India with varying interest in starting a business. An online survey instrument was used to collect the data. Regression and mediation analyses were used to analyze the data. Findings The authors find that both hostile and benevolent sexism are positively related to entrepreneurial intentions of both men and women. However, only benevolent sexism is related to both the masculine and feminine gender traits ascribed to entrepreneurs. Interestingly, the authors find support that hostile sexism is actually positively related to feminine traits ascribed to entrepreneurs, albeit with a small effect size. The authors do not find any support that these results vary by participant gender; the findings are implicated for both men and women alike. The authors find that for both hostile and benevolent sexism only the feminine traits perceived as stereotypic of entrepreneurs partly mediate their relationship on entrepreneurial intentions. Research limitations/implications The survey consists of cross-sectional, self-report data, and therefore the authors cannot conclusively infer causality. The direction of relationships found is of theoretical value. Only two countries are included in the sample limiting generalizability to other countries. Most of the participants in the sample reported some interest or experience in nascent entrepreneurial activities, which may limit the generalizability of findings to those without any prior interest or experience as a nascent entrepreneur. Originality/value The relationship between ambivalent sexism (both hostile and benevolent sexism) and both entrepreneurial intentions, and the gendered traits ascribed to entrepreneurs, has not yet been explored before this work. Using the lens of cultural masculinity, we present a theoretical model of how hostile and benevolent sexist attitudes facilitate or inhibit entrepreneurship via how entrepreneurs are perceived. This is the first study we know of which explores the relationship between Ambivalent Sexism and the gender attributes ascribed to entrepreneurs, and how these gendered entrepreneurial stereotypes in turn are related to entrepreneurial intentions.
Keywords: Ambivalent Sexism Scale; Benevolent sexism; Culture; Entrepreneurial intentions; Hostile sexism; Masculinity; Social construction of gender; dept.mgt; peer-reviewed

Risk aversion for decisions under uncertainty: Are there gender differences? - Sarin, Rakesh; Wieland, Alice (Journal of Behavioral and Experimental Economics, 2016)
It has become well accepted that women are more risk averse than men. For objective probability gambles, typically used in eliciting risk aversion, we find women generally have a lower valuation than men, thus exhibiting greater risk aversion. This paper investigates whether this finding extends to decisions under uncertainty – where probabilities are not given and individuals may assign different probabilities to the same event (e.g. outcomes of award shows or sporting events).We find that for decisions under uncertainty, men and women value the bets similarly, both before and after controlling for participants' subjective probabilities.
Keywords: Decision-making; Gender; Risk aversion; Subjective probability; Uncertainty; dept.mgt; peer-reviewed

Domain specificity of sex differences in competition - Wieland, Alice; Sarin, Rakesh (Journal of Economic Behavior & Organization, 2012)
There has been much recent literature about sex differences in competition, mostly noting that women are innately less competitive than men (Croson and Gneezy, 2009). This article examines the hypothesis that sex differences in propensity to compete are domain specific. We conducted a 2 (sex)×4 (domain) experiment with 434 participants examining competition decisions, familiarity with the domain, and performance. We find no overall sex differences in rates of competition when collapsing across all four domains, but do find sex differences in rates of competition for individual domains. Additionally we examined the importance of winning at competition on self-esteem using the Contingencies of Self-Worth, Competition subscale (Crocker et al., 2003) and find that the subscale fully mediates the effect of sex on the strength of competitive pay preferences.
Keywords: Competition; Decision-making; Gender differences; Risk; Sex differences; dept.mgt

Boosting Performance on an Evaluative Math Test: Goal Activation vs Self-Affirmation - Wieland, Alice M.; Burnham, Thomas A. (Psychological Reports, 2016)
This study compared the effectiveness of goal activation versus self-affirmation and a control condition as interventions for increasing performance on an evaluative task (a difficult math test; N = 78; M age = 20.3 yr., SD = 1.9). Although there has been much recent literature on the effects of activating goals, the existing literature does not examine possible spillover effects of activating goals on performance tasks. Results indicated that goal activation resulted in significant performance enhancements over both the self-affirmation and control conditions, while self-affirmation did not improve performance significantly relative to the control condition. Additionally, interest in the task, as a cue for self-regulatory resources, mediated the effect of goal activation on increased performance.
Keywords: dept.mgt

Gender Characterizations in Entrepreneurship: A Multi‐Level Investigation of Sex‐Role Stereotypes about High‐Growth, Commercial, and Social Entrepreneurs* - Gupta, Vishal K.; Wieland, Alice M.; Turban, Daniel B. (Journal of Small Business Management, 2019)
The purpose of this study is to cast new light on possible gender biases in implicit theories people hold about various forms of entrepreneurial activity. Using social role theory, we delve into sex‐role stereotypes associated with high‐ and low‐growth entrepreneurship and commercial and social entrepreneurship. Predictions were tested with an experimental design using both a between‐subject design to capture group‐level stereotypes and a within‐subject design to capture individual‐level stereotypes. Findings reveal that commercial and high‐growth entrepreneurs are perceived as more similar to men than to women and higher on agency than communality. Conversely, low‐growth entrepreneurs are perceived as more similar to women than men, and higher on communality than agency. Social entrepreneurs are uniquely perceived as similar to both men and women, though they are also considered higher on agency than communality. Interestingly, female, but not male respondents, perceive some overlap between the feminine gender role and high‐growth and commercial entrepreneurship. Notably, those higher on modern sexism perceive less overlap between entrepreneurship and femininity. Taken together, our results suggest that commercial high‐growth entrepreneurship is most strongly male‐typed, which is likely to be problematic for women (and non‐traditional men) wanting to start growth‐oriented ventures. Implications and directions for future research are discussed.
Keywords: dept.mgt; peer-reviewed

Designing Entrepreneurship Experiments: A Review, Typology, and Research Agenda - Hsu, Dan K.; Simmons, Sharon A.; Wieland, Alice M. (Organizational Research Methods, 2017)
This article discusses the current and potential application of experimental methods to the study of entrepreneurship phenomena. Drawing on a review of experimental studies in entrepreneurship research, we discuss the advantages and disadvantages of experimental research designs for entrepreneurship research as a primer for those interested but not overly familiar with these methods. To advance research agendas and theory in the field, we introduce a typology of experimental manipulations that highlight alternative design choices based on the nature of their participant impact and realism of context. Finally, we provide an overview of areas of opportunity within the entrepreneurship literature for application of methods best suited to provide greater insight into the causal mechanisms at play.
Keywords: dept.mgt; peer-reviewed

Antecedents of corporate entrepreneurship in Iran: the role of strategic orientation and opportunity recognition - Kakapour, Saba; Morgan, Todd; Parsinejad, Salman; Wieland, Alice (Journal of Small Business & Entrepreneurship, 2016)
In a study of 130 Iranian small- and medium-sized enterprises (SMEs), we predict and find that market orientation, learning orientation, and their interaction are positively related to opportunity recognition, which impacts firm-level corporate entrepreneurship positively. This study makes two important contributions to the corporate entrepreneurship literature. First, the majority of studies on corporate entrepreneurship concern western economies or China; as such, we broaden research on the international context of corporate entrepreneurship by examining a unique dataset of Iranian SMEs, which have grown significantly in recent years during their transition to knowledge-based enterprises. Second, we build upon previous literature on corporate entrepreneurship antecedents by explicating and testing the relationships of how and when learning orientation and market orientation affect opportunity recognition and the development of corporate entrepreneurship.
Keywords: Apprentissage organisationnel; Entreprenariat d'entreprise; Entreprises fondées sur les connaissances; Iran; Orientation de marché; Orientation sur l'apprentissage; Petites et Moyennes Entreprises; Repérage des débouchés; corporate entrepreneurship; dept.mgt; knowledge-based enterprises; learning orientation; market orientation; opportunity recognition; organizational learning; peer-reviewed; small and medium-sized enterprises

Gender differences in the endowment effect: Women pay less, but won’t accept less - Wieland, Alice; Sundali, James; Kemmelmeier, Markus; Sarin, Rakesh (Judgment and Decision Making, 2014)
We explore different contexts and mechanisms that might promote or alleviate the gender effect in risk aversion. Our main result is that we do not find gender differences in risk aversion when the choice is framed as a willingness-to-accept (WTA) task. When the choice is framed as a willingness-to-pay (WTP) task, men are willing to pay more and thus exhibit lower risk aversion. However, when the choice is framed as a willingness to accept task, women will not accept less than men. These findings imply gender differences in the endowment effect. We also find that the effect size of the gender difference in risk aversion is reduced or eliminated as the context changes from tasks framed as gambles to other domains; and that attitudes toward gambling mediate the gender effect in gambling framed tasks.
Keywords: dept.mgt; endowment effect; gambling attitudes; gender; peer-reviewed; risk attitudes; risk aversion; sex differences

Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M., Kemmelmeier ,Markus, Gupta ,Vishal K.; and McKelvey, William (Entrepreneurship & Regional Development, 2019)
This research explores the social-cognitive factors which lead both women and men to pursue ventures consistent with their gendered social identity, therefore, reinforcing the gender gap in entrepreneurship. We measured the self-assessments of individuals presented with experimentally manipulated entrepreneurial opportunities that were either consistent or inconsistent with their self-reported gender. A theoretical model derived from Social Role Theory is presented and tested. It posits that a gender match (mismatch) with the entrepreneurial opportunity results in higher (lower) reported self-efficacy, anticipated social resources, and venture desirability and lower (higher) venture risk perceptions. The experimental data are tested in a sequential mediation SEM model. We find evidence that self-efficacy and anticipated social resources mediate the effect of gender congruency on perceived risk and venture desirability. The results provide insight into the insidious barriers that play a role in reproducing a gender gap in entrepreneurial outcomes by ‘nudging’ women into lower-return ventures in less lucrative industries.
Keywords: Entrepreneur; gender; gender gap; gender norms; gender role; opportunity evaluation; sex